PENILAIAN PORTOFOLIO DALAM PEMBELAJARAN SENI - Asidigisianti Surya Patria, (Pendidikan Sekolah Dasar, 2010)
Classroom based assessment is an assessment intergerated with learning and teaching in the classroom. One of assessment based on classroom is by gathering student works or called portfolio. The ability of portfolio assessment is as communication media refleceting student capability during learning process. Portfolio assessment is able to reveal learning development, not only measured by paper test  but showed from evidences in the portfolio. Beside teacher, parents can also see the devolement of their children through evidences.In art, portfolio is used as assessment in learing process specially in studio classes in Art College.